Decision-Making in Cleft-Related Surgery: A Qualitative Analysis of Patients and Caregivers. (February 2020) - Bennett, Katelyn G.; Patterson, Annie K.; Schafer, Kylie; Haase, Madeleine; Ranganathan, Kavitha; Carlozzi, Noelle; Vercler, Christian J.; Kasten, Steven J.; Buchman, Steven R.; Waljee, Jennifer F.
Objective: Preference-sensitive surgical decisions merit shared decision-making, as decision engagement can reduce decisional conflict and regret. Elective cleft-related procedures are often preference sensitive, and therefore, we sought to better understand decision-making in this population. Design: Semistructured interviews were conducted to elicit qualitative data. A hierarchical codebook was developed through an iterative process in preparation for thematic analysis. Thematic analysis was performed to examine differences between patients and caregivers. Setting: Multidisciplinary cleft clinic at a tertiary care center. Participants: Patients with cleft lip aged 8 and older (n = 31) and their caregivers (n = 31) were purposively sampled. Inability to converse in English, intellectual disability, or syndromic diagnoses resulted in exclusion. Main Outcome Measures: Preferences surrounding surgical decision-making identified during thematic analysis. Results: Mean patient age was 12.7 (standard deviation: 3.1). Most had unilateral cleft lip and palate (43.8%). Three themes emerged: Insufficient Understanding of Facial Difference and Treatment, Diversity of Surgical Indications, and Barriers to Patient Autonomy. Almost half of caregivers believed their children understood their clefts, but most of these children failed to provide information about their cleft. Although many patients and caregivers acknowledged that surgery addressed function and/or appearance, patients and caregivers exhibited differences regarding the necessity of surgery. Furthermore, a large proportion of patients believed their opinions mattered in decisions, but less than half of caregivers agreed. Conclusions: Patients with clefts desire to participate in surgical decisions but have limited understanding of their facial difference and surgical indications. Cleft surgeons must educate patients and facilitate shared decision-making.